The Effect of Benson Relaxation on Insomnia among Elderly - Agusti, Agusti; Anggraini, Rima Berti; Ardiansya, Ardiansya (Inspirasi Foundation, 2026)
Introduction: Insomnia is a common sleep disorder among elderly and is associated with physical, psychological, and functional decline. The prevalence of insomnia increases with aging and may negatively affect quality of life if left untreated. Non-pharmacological interventions are recommended as safe and effective strategies to improve sleep quality in the elderly. One such intervention is the Benson Relaxation Technique, which promotes relaxation through controlled breathing and mental focus. This study aims to examine the effect of Benson Relaxation Therapy on insomnia in elderly. Objective: This study aimed to determine the effect of Benson relaxation therapy on insomnia in the elderly at the Simpang Rusa Community Health Center, Belitung. Method: The study design used a pre-experimental study with a pre-test and post-test in one group. A total of 10 elderly individuals received Benson relaxation therapy for one week. Insomnia levels were measured using the Toward Optimized Practice (TOP) screening questionnaire and analyzed using the Wilcoxon test. Result: The results showed a significant decrease in insomnia levels after the intervention. The Z-value was -2.814 with a significance value of p = 0.005 (<0.05), indicating that Benson relaxation therapy significantly reduced insomnia in the elderly. Conclusion: From these results, it can be concluded that Benson relaxation therapy is effective in improving sleep quality in the elderly with insomnia. It is recommended that the elderly practice Benson relaxation independently and regularly. Community health centers (Puskesmas) consider this therapy as a non-pharmacological intervention in elderly healthcare. Further research is recommended to combine Benson relaxation with aromatherapy for optimal results.